A study on the effect of emulsion concentration and microwave output power levels on microwave heating and separation of water-in-oil emulsions - 387312 Mohd. Johari Kamaruddin (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2005